Intravitreal ranibizumab therapy for retinal arterial macroaneurysm - Erol, Muhammet Kazim (Int J Clin Exp Med, 2015)
Aim: To evaluate the anatomic and functional results of intravitreal ranibizumab injection for treatment of symptomatic retinal arterial macroaneurysm (RAM). Materials and Methods: A series of seven patients (seven eyes) who had been diagnosed with symptomatic RAM were assessed by comprehensive ophthalmologic examination, fluorescein angiography (FA), optical coherence tomography (OCT), and indocyanine green angiography (ICGA). All patients were treated by intravitreal ranibizumab injection within one week of diagnosis and retreated upon evidence of persistent serous detachment or hemorrhage involving the macula on OCT. Anatomical recovery was examined by FA, OCT, and ICGA. Best-corrected visual acuity (BCVA) and central macular thickness (CMT) were evaluated using the Snellen chart and optical coherence tomography, respectively, at baseline; at 1, 3, and 6 months; and at the final visit. The BCVA and CMT values at baseline and the final visit were compared using the Wilcoxon signed rank test and determination of logarithm of the minimal angle of resolution (logMAR) of BCVA value. Results: Over a mean follow-up period of 10.86 ± 5.4 months, significant visual and anatomical recovery was observed, with visual acuity improving by three or more lines in all seven patients. The mean logMAR of BCVA improved from 1.09 ± 0.60 to 0.16 ± 0.16 (p = 0.018) and mean CMT decreased from 427.5 ± 132.4 μm to 208.7 ± 23.1 μm (P = 0.018). No complications were observed with intravitreal ranibizumab injection. Conclusion: İntravitreal ranibizumab is an effective therapy for symptomatic RAM, improving BCVA and decreasing CMT.